DeAR: Combining Desktop and Augmented Reality for Visual Data Analysis - Iquiapaza, Yhonatan; Wagner, Jorge; Nedel, Luciana (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2023)
Combining different interfaces and displays might enhance the capabilities of data analysis, particularly in the context of Immersive Analytics. In this work, we design a prototype, called DeAR (Combining Desktop and Augmented Reality for Visual Data Analysis), which integrates a desktop environment with an augmented reality one. DeAR enables users to interact with both environments simultaneously, facilitating visualizations comparisons and diverse data analysis tasks. With our prototype, users can interact with two visualization paradigms, with changes made to visualizations in one being reflected in the other. We describe a use case scenario to demonstrate how our proposed design could facilitate exploration and selection tasks. The primary contribution of our work lies in the design and implementation of a proof-of-concept prototype, named DeAR, that allows interaction with data in hybrid environments. This prototype combines heterogeneous interfaces and displays, providing new opportunities for data analysis.